Curing Medicare : a doctor's view on how our health care system is failing older Americans and how we can fix it - Lazris, Andrew (Culture and politics of health care work., 2016)
Maintains that the current Medicare payment structure favors aggressive care that can negatively impact quality of life over palliative and home care which often yields better results, and argues for cost-effective changes that can make Medicare more humane.